Empowering Unprosperous Communities Through A Creative Economy Based On Household Waste Processing - Muhammad Haris; Tri Indah Epril Lilawati; Muhammad Mochtar Mas'od; Fernando Yudistira (UIN Siber Syekh Nurjati Cirebon, 2025)
Structural poverty experienced by underprivileged communities remains a complex social problem, characterized by limited access to jobs, skills, and markets. One strategic approach to addressing this issue is community empowerment through the development of a creative economy based on local potential. This study aims to describe the process of empowering underprivileged communities through creative economy activities, including program socialization, skills training, and product marketing. The study employed a qualitative method with a descriptive approach. Data were collected through participant observation, structured interviews, and documentation, then analyzed using qualitative descriptive analysis techniques with data triangulation to increase the validity of the findings. The theoretical foundation of this study rests on the theories of community empowerment, the creative economy, and local potential-based capacity development. The results show that program socialization plays a crucial role in increasing community awareness and participation in the potential of the creative economy, particularly in the utilization of household waste. Hands-on skills training has been shown to enhance participants' creativity, technical skills, and confidence in producing marketable products. Furthermore, marketing strategies through digital marketing and the use of e-commerce platforms such as Shopee contribute to expanding market reach and increasing product competitiveness, despite the ongoing constraints of limited internet access. Overall, this study confirms that the integration of socialization, skills training, and marketing is a key factor in encouraging economic independence and the sustainable empowerment of underprivileged communities through the creative economy.